The Impact of Facilities and Service Quality on the Satisfaction of Hemodialysis Patients at Mitra Jatiasih Hospital - Labiba, Salsabil Inas; Zaharuddin, Zaharuddin; Junaedi, Dudun (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The advancement of science and technology has increased public awareness of healthy living, establishing health as a critical foundation for social and economic stability. Hospitals, therefore, play a central role in providing high-quality healthcare services that influence patient satisfaction. This study aims to analyze the influence of facilities and service quality on the satisfaction of hemodialysis patients at Mitra Jatiasih Hospital. A quantitative approach with a descriptive-correlational design was employed, involving all 72 hemodialysis patients as research subjects through total sampling. Data were collected using validated and reliable questionnaires and analyzed with multiple linear regression supported by classical assumption tests. The results showed that facilities had a significant positive effect on patient satisfaction, contributing 17.4%, while service quality also had a significant impact with a 13.2% contribution. Simultaneous testing revealed that both variables collectively accounted for 39.5% of the variation in patient satisfaction. These findings underscore that improvements in infrastructure and the quality of service delivery are critical to enhancing satisfaction among patients undergoing long-term treatment. In conclusion, the study confirms that better facilities and optimal service quality lead to higher satisfaction levels, emphasizing the need for hospital management to prioritize these areas in delivering patient-centered care.